Leaning into the Spirit: Ecumenical Perspectives on Discernment and Decision-making in the Church - Miller, Virginia; Moxon, David; Pickard, Stephen K. (Pathways for Ecumenical and Interreligious Dialogue, 2019)
1. Introduction – Virginia Miller and David Moxon -- 2. Spirit Christology: Rethinking Christo-Centric Theology – Michael Welker -- 3. God’s Spirit, the Human Spirit, and the Outpouring of the Spirit – Michael Welker -- 4. Theological Horizons for an Ecumenical Future: a response to Michael Welker – Stephen Pickard -- 5. A Critical Reflection of the Role of 'Context' in Discernment, Decision-making, and Reception – Mary-Anne Plaatjies-Van Huffel -- 6. Receptive Ecumenism in Africa: Lessons Learned from the Actual Faith of Everyday Christians – Stan Chu Ilo -- 7. Ecumenical Thrusts for Discernment from the Perspectives of the Indian Subcontinent – Paul Pulikkan -- 8. Chiara Lubich and Decision-making: a Spiritual Methodology of Mutual Reception Based on Christ Crucified and Forsaken – Callan Slipper -- 9. The Church Local, Regional and Universal: A Delicate Balance. A Recent Ecclesiological Statement of ARCIC III - Adelbert Denaux -- 10. United not Absorbed: The Malines Conversation Revisited – Keith Pecklers -- 11. The Anniversary of the Reformation as a Moment for Ecclesial Learning – Gerard Kelly -- 12. Receptive Ecumenism in the Context of Bilateral Dialogues - Ray Williamson -- 13. Reconciling Theology – Three Concepts for Convergence – Paul Avis -- 14. A Ministry of Mary? The Question of the Ordination of Women Revisited in Light of the Theology of Complementarity – Virginia Miller -- 15. Ecumenism for a Global Church: Can the Churches of the West and those of the Global South Learn From Each Other? – Thomas Rausch -- 16. Discerning the Call of the Spirit to Theological-Ecclesial Renewal: Notes on Being Reasonable and Responsible in Receptive Ecumenical Learning – Paul D. Murray -- 17. Does Receptive Ecumenism Have a Future? – Peter Carnley.